An extended model of value-attitude-behavior to explain Chinese consumers' green purchase behavior. (September 2019) - Cheung, Millissa F.Y.; To, W.M.
Abstract: This study proposed an extended value-attitude-behavior model to explain for consumers' green purchase behavior and validated this model on a random sample of 399 Chinese consumers in Hong Kong. Results of structural equation modelling showed that consumers' environmental consciousness (value) strongly influenced their attitude towards environmental issues and towards eco-social benefits (attitude), which in turn exerted positive effects on their green purchase behavior (behavior). Green product information was found to be a key determinant of consumers' green purchase behavior. Moreover, high quality green products were reported to moderate the relationships between attitude towards eco-social benefits and green purchase behavior and between green product information and green purchase behavior, but not on the relationship between attitude toward environmental issues and green purchase behavior.